1957
DOI: 10.1037/h0047232
|View full text |Cite
|
Sign up to set email alerts
|

A study of anxiety in the sociopathic personality.

Abstract: As compared with 15 normal controls, " "primary' sociopaths showed significantly less "anxiety' on a questionnaire device, less GSR reactivity to a "conditioned' stimulus associated with shock, and less avoidance of punished responses on a test of avoidance learning. The "neurotic' sociopaths scored significantly higher on the Taylor Anxiety Scale and on the Welsh Anxiety Index." Cleckley's descriptive criteria were used. 24 references.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

44
606
3
21

Year Published

1960
1960
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,102 publications
(674 citation statements)
references
References 20 publications
44
606
3
21
Order By: Relevance
“…Because the ASD-group activated the right insula more than the PSY-group this could reflect that exposure to fearful facial expressions is associated with more bodily arousal in the ASD-group compared to the PSY-group. This reasoning is in line with earlier studies showing that psychopathic subjects have lower autonomic responses during exposure to emotionally relevant information [43,[48][49][50][51][52]. The PSY-group had higher activation in the ACC compared to the ASD-group which could be connected to the possible inhibition of amygdala reactivity.…”
Section: Discussionsupporting
confidence: 80%
“…Because the ASD-group activated the right insula more than the PSY-group this could reflect that exposure to fearful facial expressions is associated with more bodily arousal in the ASD-group compared to the PSY-group. This reasoning is in line with earlier studies showing that psychopathic subjects have lower autonomic responses during exposure to emotionally relevant information [43,[48][49][50][51][52]. The PSY-group had higher activation in the ACC compared to the ASD-group which could be connected to the possible inhibition of amygdala reactivity.…”
Section: Discussionsupporting
confidence: 80%
“…Conversely, O'Brien and Frick (1996) found that anxious children who exhibited psychopathic features did not differ from the control group, and their results are consistent with Gray's (1982) psychobiological theory of personality (O'Brien & Frick, 1996). Lykken (1957) proposed that individuals with psychopathic traits were unresponsive to punishment cues and demonstrated deficits in passive avoidance learning, where behavior elicited by a stimulus is halted on the basis of the resultant punishment of the response. As such, he suggests that the techniques relying on the fear of punishment would be ineffective in the modification of behavior with psychopathic individuals (Lykken, 1957).…”
Section: Callous and Unemotional Children's Sensitivity To Reward Andsupporting
confidence: 57%
“…RHA-I and RLA-I) strains, which have been psychogeneticallyselected for their extreme responses in anxiety-related tasks, the low anxious (and high impulsive) RHA-I strain do not show fear-induced potentiation of startle in a typical cue-conditioning procedure, while the relatively high anxious (and low impulsive) RLA-I strain show clear fear-potentiated startle responses [12]. Second, some seminal conditioning studies in psychopaths using single cue paradigms and electrodermal activity showed less conditioning in these subjects compared with control participants [16,17], and recent studies have also shown that psychopathic and antisocial individuals do not show increased skin conductance responses to CS+ stimuli in differential conditioning paradigms [18,19]. Thus, antisocials, psychopaths and low trait-anxiety subjects could share an endophenotype related to vulnerability for a deficient excitatory conditioning to danger cues.…”
Section: Discussionmentioning
confidence: 99%